PM2.5 Pollution Modulates Wintertime Urban Heat Island Intensity in the Beijing‐Tianjin‐Hebei Megalopolis, China. Issue 1 (17th January 2020) - Yang, Yuanjian; Zheng, Zuofang; Yim, Steve Y.L.; Roth, Matthias; Ren, Guoyu; Gao, Zhiqiu; Wang, Tijian; Li, Qingxiang; Shi, Chune; Ning, Guicai; Li, Yubin
Abstract: Heavy PM2.5 (particulate matter with aerodynamic diameter equal to or less than 2.5 μm) pollution and urban heat island (UHI) pose increasing threats to human health and living environment in populated cities. However, how PM2.5 pollution affects the UHI intensity (UHII) has not been fully understood. The impacts of PM2.5 on the wintertime UHII in the Beijing‐Tianjin‐Hebei megalopolis of China are explored during 2013–2017. The results show that the UHII at the time of daily maximum/minimum temperature (UHIImax /UHIImin ) exhibits a decreasing/increasing tendency as PM2.5 concentration increases, causing a continuous decrease in the diurnal temperature range. These effects are mediated via aerosol‐radiation interaction (aerosol‐cloud interaction) under clear‐sky (cloudy) condition. The changes in PM2.5 concentration further cause different relative trends of UHIImax /UHIImin /diurnal temperature range across different cities in the Beijing‐Tianjin‐Hebei region, which are likely related to the differences in both the PM2.5 composition and city size. This study provides insights on how air pollution affects urban climate and would help to design effective mitigation strategies. Plain Language Summary: A detailed understanding of the relationship between PM2.5 (particulate matter with aerodynamic diameter equal to or less than 2.5 μm) and the urban heat island (UHI) effect is significant for climate change adaption, planning, and sustainable development in urban regions. While the Beijing‐Tianjin‐Hebei (BTH) megalopolis of China is among the areas with the highest population densities and fastest urbanization rates in the world, the impacts of PM2.5 pollution on UHI, along with their regional differences in the BTH megalopolis, remain unclear. This study demonstrates that different PM2.5 concentrations in the BTH region pose various influences on the UHI intensities and their change rates in different cities of varying sizes. The UHI intensities during daytime and nighttime, respectively, exhibit weakening and strengthening tendency as PM2.5 concentration increases. These effects are mediated via aerosol‐radiation interaction under clear‐sky condition and aerosol‐cloud interaction in cloudy weather. The relative changes in the UHI magnitudes were mainly determined by PM2.5 composition and city size. The asymmetrical influences of PM2.5 on the daytime and nighttime UHI intensities caused continuous decreases in the diurnal temperature ranges in the urban areas as the pollution level increased. Our study improves the understanding of urban climate affected by air pollution and provides a scientific basis for the mitigation of UHI impacts. Key Points: Given a similar change in PM2.5 pollution levels, the relative change in UHII is determined by both PM2.5 species and city size With increasing PM2.5 in the urban area, daytime UHII weakens and nighttime UHII strengthens, leading to a continuous reduction in DTR PM2.5 affects UHII via aerosol‐radiation interaction under the clear sky and via aerosol‐cloud interaction under cloudy condition